2009
DOI: 10.1121/1.3204087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of boundary slip on the acoustical properties of microfibrous materials

Abstract: A variety of new porous materials with unusually small pores have been manufactured in the past decades. To predict their acoustical properties, the conventional models need to be modified. When pore size becomes comparable to the molecular mean free path of a saturating fluid, the no-slip conditions on the pore surface are no longer accurate and hence the slip effects have to be taken into account. In this paper, sound propagation in microfibrous materials is modeled analytically, approximating the geometry b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…The results gathered are consistent with this hypothesis, but the conclusive proof of what causes the change in surface reactance remains elusive. It is still conceivable that other phenomena, such as multi-scale porosity, slip flow, 20 or gas diffusion, might play a part. Whatever the cause, this study has confirmed that activated carbon can be used to change the compliance of enclosures, and to enable higher absorption at a lower frequency than would otherwise be expected from conventional porous absorbers.…”
Section: Discussionmentioning
confidence: 99%
“…The results gathered are consistent with this hypothesis, but the conclusive proof of what causes the change in surface reactance remains elusive. It is still conceivable that other phenomena, such as multi-scale porosity, slip flow, 20 or gas diffusion, might play a part. Whatever the cause, this study has confirmed that activated carbon can be used to change the compliance of enclosures, and to enable higher absorption at a lower frequency than would otherwise be expected from conventional porous absorbers.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal slip effects modify the dynamic bulk modulus but not its static value 46,47 Mass transfer processes also alter the dynamic bulk modulus. For example, Raspet et al 49 have studied the sound attenuation in rigid cylindrical pores filled with air and saturated water vapor accounting for the mass transfer of vapor from the wet tube wall.…”
Section: Comparison With Datamentioning
confidence: 99%
“…Considering that the molecular mean free path l mean is approximately 60 nm at normal conditions, 47 the calculation of the static viscous . The agreement between the double porosity model and the data is better than that for the single porosity model.…”
Section: Comparison With Datamentioning
confidence: 99%
“…(44), (46), and (55)-(58) from Ref. 21 and assuming than Knudsen number K ¼ 0 (i.e., that the cylinders and the distances between them are large compared to the molecular mean free path). This results in the following expressions:…”
Section: Model Validationmentioning
confidence: 99%